Similarity- and substructure-based development of β2-adrenergic receptor ligands based on unusual scaffolds - Schmidt, Denis; Gunera, Jakub; Baker, Jillian G.; Kolb, Peter (American Chemical Society, 2017)
The β2-adrenergic receptor (β2AR) is a G protein-coupled receptor (GPCR) and a well-explored target. Here, we report the discovery of 13 ligands, ten of which are novel, of this particular GPCR. They have been identified by similarity- and substructure-based searches using multiple ligands, which were described in an earlier study, as starting points. Of note, two of the molecules used as queries here distinguish themselves from other β2AR antagonists by their unique scaffold. The molecules described in this work allow us to explore the ligand space around the previously reported molecules in greater detail, leading to insights into their structure−activity relationship. We also report experimental binding and selectivity data and putative binding modes for the novel molecules.